What Principles of Multimedia Learning Do Language Instructional Designers Need to Know? - Ansyari, Muhammad fauzan (Journal of English and Arabic Language Teaching, 2017)
One of the trends in educational technology is multimedia. Instructional material designers or developers often ignore the principles of learning with multimedia in the creation of learning materials. Therefore, the aim of the given paper is to discuss the principles of multimedia learning material design to help students learn better. This includes Dual Coding Theory (DTC), Cognitive Load Theory (CLT), and Mayer‘s principles of multimedia design.